ADWE-09 Low fodmap diet improves functional-like gastrointestinal symptoms but reduces bifidobacteria in quiescent inflammatory bowel disease. (8th June 2018) - Cox, Selina; Stagg, Andrew; Fromentin, Sebastién; Ehrlich, Dusko; McCarthy, Neil; Galleron, Nathalie; Levenez, Florence; Lomer, Miranda; Lindsay, James; Irving, Peter; Whelan, Kevin
Abstract : Introduction: Many patients with quiescent inflammatory bowel disease (IBD) also experience functional-like GI symptoms. The low FODMAP diet improves GI symptoms in quiescent IBD in uncontrolled trials but there are no placebo-controlled trials to confirm this. We performed a randomised, placebo-controlled trial to assess the effects of a low FODMAP diet on GI symptoms, microbiota, inflammatory markers and circulating gut-tropic (α4β7+) T-cells in patients with quiescent IBD. Methods: Patients with Crohn's disease (CD) or ulcerative colitis (UC) were included. Quiescent IBD was defined as: 1) Physician Global Assessment, 2) faecal calprotectin [FC]<250 µg/g and 3) CRP <10 mg/L. Suitable patients fulfilled the Rome III criteria for IBS, functional bloating or functional diarrhoea, and were naïve to the low FODMAP diet. Participants were randomised to low FODMAP or placebo (sham) dietary advice for 4 weeks. At baseline and end of trial, GI symptoms and stool output were measured using validated questionnaires. Faecal microbiota were characterised using metagenomic sequencing and α4β7+T cell populations quantified using flow cytometry. End of trial data were compared intention to treat between the diets using analysis of covariance adjusting for baseline values. Results: Fifty two patients were randomised (27 low FODMAP diet, 25 sham diet). At the end of trial, more patients reported adequate relief of GI symptoms following the low FODMAP diet (14/27, 52%) than the sham diet (4/25, 16%) (p=0.007). Total IBS Severity Scoring System score decreased by 67 points (SD 78) during the low FODMAP diet and 34 points (SD 50) during the sham diet (p=0.075). Daily stool frequency was lower following low FODMAP diet (1.7 SD 0.5) than sham diet (2.1 SD 0.5) (p=0.012). Bacterial gene richness was not different between the groups at end of trial (p=0.620). Relative abundance of Bifidobacterium longum (1.24– 7 vs 6.95– 7, p=0.003) and B. adolescentis (1.99– 7 vs 2.55– 6, p=0.015) was lower following low FODMAP diet compared to sham diet. Between baseline and end of trial, Faecalibacterium prausnitzii SL3/3 M21/2 (2.30– 6 vs 1.52– 6, p=0.029) and F. prausnitzii KLE1255 (4.49– 6 vs. 2.68– 6, p=0.006) declined in the low FODMAP diet group. There was no difference in proportions of α4β7+T cells between groups at end of trial. Conclusions: The low FODMAP diet improved functional-like GI symptoms in patients with quiescent IBD but reduces immunoregulatory species of the intestinal microbiota, though does not impact on inflammatory markers or α4β7+blood T-cell numbers.